(E)-4-Methoxy-2-(o-tolyliminomethyl)phenol - Özek, Arzu (International Union of Crystallography, 2009)
In the molecule of the title compound, C(15)H(15)NO(2), the aromatic rings are oriented at a dihedral angle of 15.46 (6)°. An intramolecular O—H⋯N hydrogen bond results in the formation of a nearly planar six-membered ring [maximum deviation of 0.035 (5) Å for the N atom] which is almost coplanar with the adjacent ring, making a dihedral angle of 0.8 (3)°. The title organic molecule is a phenol–imine tautomer, as evidenced by the C—O, C—N and C—C bond lengths. Molecules are linked by intermolecular C—H⋯O hydrogen bonds that generate a C(5) chain. C—H⋯π and π–π interactions exist in the structure. The π–π interaction occurs between the phenol ring and its symmetry equivalent at (1 − x, 1 − y, −z), with a centroid–centroid distance of 3.727 (7) Å and a plane-to-plane separation of 3.383 (5) Å, resulting in an offset angle of 24.82 (1)°.